2022
DOI: 10.2147/cia.s368219
|View full text |Cite
|
Sign up to set email alerts
|

Association of Elevated Thyroid Stimulating Hormone with Atherosclerotic Cardiovascular Disease and Its Mortality in Elderly Community-Dwelling Chinese

Abstract: Purpose With increase of population aging, the prevalence of atherosclerotic cardiovascular disease (ASCVD) and elevated serum thyroid stimulating hormone (TSH) in elderly is increasing. High TSH level was reported to be associated with ASCVD and CVD mortality; however, few are studied in Chinese population, especially in the elderly. This study aimed to investigate the prevalence of elevated serum TSH and ASCVD in an elderly population of Chinese community and to explore the association between h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Low TH levels possibly contribute to the increase in systematic vascular resistance and cause endothelial changes by decreasing nitric oxide availability ( 37 ). Therefore, it was suggested that thyroid hormone administration in SHypo subjects could improve serum lipid profile and other cardiovascular risk factors, thereby decreasing cardiovascular risks ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low TH levels possibly contribute to the increase in systematic vascular resistance and cause endothelial changes by decreasing nitric oxide availability ( 37 ). Therefore, it was suggested that thyroid hormone administration in SHypo subjects could improve serum lipid profile and other cardiovascular risk factors, thereby decreasing cardiovascular risks ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%